Concentración y rentabilidad en la banca múltiple peruana: 2001 - 2016 - Echevarría Marcelo, Fiorella Del Milagro (2016)
This research aims to determine how bank concentration is related to the profitability of Peruvian multiple banks for the period 2001-2016. The hypothesis of "structure-behavior-performance" and the "efficiency hypothesis" is used as the theoretical framework. The econometric estimates were based on monthly time series from 2001 to 2016. The data were obtained from the Superintendence of Banking and Insurance. We specified a linear regression whose parameters were estimated using the cointegration technique, through an Error Correction Vector (VEC). The results show that there is a positive relationship between concentration and bank profitability, for each increase of one point in the HHI, ROE increases by 0.07 percentage points. The findings also confirm that efficiency gains increase the profitability of banks.